FINANCIAL VIABILITY OF IRRIGATED COFFEE PRODUCTION IN REGIONS SUITABLE FOR CULTIVATION WITHOUT IRRIGATION - Pêgo Evangelista, Adão Wagner; Lima, Luiz Antônio; da Silva, Antônio Carlos; Martins, Carla de Pádua (Coffee Science - ISSN 1984-3909, 2011)
Due to new economic order, agricultural business is of the same complexity, importance and dynamics of other sectors of theeconomy, requiring farmers to have a new outlook on how to run their business. Thus, it becomes necessary to economicaly analyze theactivity you begin to know the details and to use the production factors intelligently and cost efficiently. Therefore, this study aimed to estimatethe cost of production of arabica coffee (Coffea arabica L.) irrigated with a central pivot in the region of Lavras, MG. The experimental designwas randomized blocks with six treatments and three repetitions. The treatments consisted of water levels applied according to thepercentages of crop coefficients values (Kc), currently used by irrigators in the region of Lavras, and evapotranspiration reference (ET0),that is: Tr1 = 0; Tr2 = 60%KcET0, Tr3 = 80%KcET0, Tr4 = 100% KcET0, Tr5 = 120% KcET0 e Tr6 = 140%KcET0 . For the process ofestimating the cost of production, conceptualized as the sum of values of all resources and operations used in the production process of theactivity, we used the calculation of depreciation and alternative cost. The average productivity achieved with the treatments was 29.31, 39.51,51.12, 60.65, 63.82 and 74.84 bags per hectare for Tr1, Tr2, Tr3, TR4, TR5 and Tr6 respectively. Considering the price of a bag of coffee at$ 250.00, the economic analysis showed that, at this price level, irrigated coffee production is economically viable, and irrigation management,with water replacement calculated based on 100 % of the value of Kc, resulted in higher profits